PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE PADA PELAJARAN BAHASA INDONESIA SISWA KELAS IV SDN 004 PAGARAN TAPAH DARUSSALAM - Iriani, Sri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This study is a class action (class action reseach). The background of this study is the low reading comprehension, it is evident from the 18 students only five students are able to comprehend reading text in a story. For that research by applying cooperative learning model think Paire share. The aim to determine the increase in reading comprehension. This research is a class act who performed at SDN 004 Tapah Pagaran Darussalam, the study was conducted in two cycles. The data collection technique used is the technique of teacher and student activity observation and written tek. Based on the survey results revealed that students 'reading comprehension increased in each cycle, the prasiklus known that the average value of students' reading comprehension is 64.00 in the first cycle increased to 76.60 and the second cycle an increase in the average value the ability of students' reading comprehension at 86.80.